Development and validation of HPTLC and green HPLC methods for determination of furosemide, spironolactone and canrenone, in pure forms, tablets and spiked human plasma. (16th July 2018) - Naguib, Ibrahim A.; Abdelaleem, Eglal A.; Emam, Aml A.; Ali, Nouruddin W.; Abdallah, Fatma F.
Abstract: Two selective and accurate chromatographic methods are presented for simultaneous quantitation of spironolactone (SP) and furosemide (FR) and canrenone (CN), the main degradation product and the main active metabolite of SP. Method A was HPTLC, where separation was completed on silica gel HPTLC F254 plates using ethyl acetate–triethylamine–acetic acid (9:0.7:0.5, by volume) as a developing system and UV detection at 254 nm. Method B was a green isocratic RP‐HPLC utilizing a C18 (4.6 × 100 mm) column, the mobile phase consisting of ethanol–deionized water (45: 55, v /v) and UV estimation at 254 nm. Adjustment of flow rate at 1 mL/min and pH at 3.5 with glacial acetic acid was done. Regarding the greenness profile, the proposed RP‐HPLC method is greener than the reported one. ICH guidelines were followed to validate the developed methods. Successful applications of the developed methods were revealed by simultaneous determination of FR, SP and CN in pure forms and plasma samples in the ranges of 0.2–2, 0.05–2.6 and 0.05–2 μg/band for method A and 5–60, 2–60 and 2–60 μg/mL for method B for FR, SP and CN, respectively.